Pilot study of the diagnostic utility of 89Zr‐df‐IAB2M and 68Ga‐PSMA‐11 PET imaging and multiparametric MRI in localized prostate cancer. Issue 4 (5th January 2022) - Vlachostergios, Panagiotis J.; Niaz, Muhammad J.; Thomas, Charlene; Christos, Paul J.; Osborne, Joseph R.; Margolis, Daniel J. A.; Khani, Francesca; Bander, Neil H.; Scherr, Douglas S.; Tagawa, Scott T.
Abstract: Background: Accurate diagnosis of localized prostate cancer (PCa) is limited by inadequacy of multiparametric (mp) MRI to fully identify and differentiate localized malignant tissue from benign pathologies. Prostate‐specific membrane antigen (PSMA) represents an excellent target for molecular imaging. IAB2M, an 85‐kD minibody derived from a de‐immunized monoclonal antibody directed at the extracellular domain of human PSMA (huJ591), and PSMA‐11, a small molecule ligand have been previously tested as probes for visualization of recurrent/metastatic PCa with PET/CT. This pilot, non‐randomized trial studied their diagnostic utility in patients (pts) with localized PCa. Methods: Pts planned for radical prostatectomy (RP) were enrolled and underwent mpMRI and PET/CT imaging with 89 Zr‐df‐ IAB2M and/or 68 Ga‐PSMA‐PET/CT. Image results were read by a radiologist blinded to clinical information and pathology results, mapped and compared to corresponding histopathology findings from all lesions, both clinically significant and nonsignificant. The detection rates of all three imaging modalities were measured and correlated. Results: 20 pts with median age of 64.5 (46–79) years and PSA level of 7.5 (1.6–36.56) ng/ml were enrolled. 19 pts underwent RP and were imaged pre‐operatively with 89 Zr‐Df‐IAB2M PET/CT and mpMRI. Nine of those were imaged using 68 Ga‐PSMA‐11 as well. Out of 48 intraprostatic lesions verified on surgical pathology, IAB2M PET/CT was able to detect 36 (75%). A similar proportion of pathologically confirmed, clinically significant lesions (22/29, 76%) was detected. IAB2M PET/CT was also able to identify 14/19 (74%) extraprostatic lesions. The performance of mpMRI was inferior, with 24/48 detectable lesions (50%) and 18/29 clinically significant intraprostatic lesions (62%). Compared to the current standard (mpMRI), IAB2M PET/CT had a sensitivity of 88%, specificity 38%, positive predictive value 58%, and accuracy 63%. In 9 pts who underwent Ga‐PSMA‐11 as well, the latter yielded a detection rate of 70% (14/20), which was also seen in clinically significant lesions (10/14, 71%). Ga‐PSMA‐11 PET/CT also detected 4/6 (67%) extraprostatic lesions. Conclusions: In this pilot study, the performance of 89 Zr‐df‐IAB2M was superior to mpMRI and similar to 68 Ga‐PSMA‐11 PET/CT. The higher detection rate of PSMA‐PET supports its use as a diagnostic tool with consequent management change implications in men with localized PCa.